Management of Deep Neck Abscess Cases Accompanied by Comorbid Renal Failure - Sari Ratunanda, Sinta; Alkatirie, Sania Taufik; Sudiro, Melati (RSUP Dr. Kariadi, 2023)
Background: Deep neck abscess is a life threatening disease as its complications. Some comorbidities affect the successful management of deep neck abscess. Kidney failure is one of comorbidities causing uremia which in turn affecting imbalance of pro and anti inflammatory mediators. Aims: To describe the proper management of deep neck abscess comorbids with kidney failure.Case Report: To report series of deep neck abscess comorbids with kidney failure being administered therapies with various outcomes.Method: Evidence based -literature review about deep neck abscess comorbids with kidney failure was conducted in Pubmed, Clinical Key, and Google Scholar. Retrieved articles were then critically appraised.Results: Three evidence based-articles meeting criteria were included. The management of neck abscess comorbids with renal failure starts from kidney management according to Kidney disease: Improving Global Outcome (KDIGO) year 2012, and followed by management of deep neck abscess except in emergency situation. Diagnose and management of kidney disease need series examination of serume creatinine and urine monitoring.Conclusion: The management of deep neck abscess comorbids with kidney failure commences with therapy for renal failure followed by management of deep neck abscess.